2006
DOI: 10.2106/jbjs.e.01327
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcome and Risk of Recurrent Instability After Primary Traumatic Anterior Shoulder Dislocation in Young Patients

Abstract: Recurrent instability and deficits of shoulder function are common after primary nonoperative treatment of an anterior shoulder dislocation. There is substantial variation in the risk of instability, with younger males having the highest risk and females having a much lower risk. Future clinical trials to evaluate primary interventions should evaluate the prevalence of recurrent instability and functional deficits, with use of an assessment tool specifically for shoulder instability, during the first two years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
262
1
12

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 383 publications
(291 citation statements)
references
References 35 publications
9
262
1
12
Order By: Relevance
“…Redislocation rates in this high-risk patient population have been reported as high as 90% after non-operative treatment [3]. Robinson et al reported that out of 252 patients aged 15-35 years old, 53.2% experienced a repeat dislocation (134 patients), or recurrent subluxation (16 (6.5%) patients), after a mean of 13.3 months [15]. Some studies have reported even lower rates of recurrence in young populations.…”
Section: Indications/contraindicationsmentioning
confidence: 97%
“…Redislocation rates in this high-risk patient population have been reported as high as 90% after non-operative treatment [3]. Robinson et al reported that out of 252 patients aged 15-35 years old, 53.2% experienced a repeat dislocation (134 patients), or recurrent subluxation (16 (6.5%) patients), after a mean of 13.3 months [15]. Some studies have reported even lower rates of recurrence in young populations.…”
Section: Indications/contraindicationsmentioning
confidence: 97%
“…Therefore, we have to look to other literature for insight. For example, in young, active patients with shoulder instability, numerous studies implicate patient age and activity level as risk factors for Bankart repair failure and recurrent dislocation [11,14,22,28]. Specifically, studies find recurrent dislocation after shoulder stabilization to be higher in patients younger than 20 years old when compared to patients in their 20s and 30s [11,28].…”
Section: Introductionmentioning
confidence: 99%
“…contato, acometimento do membro dominante, tempo e tipo de imobilização utilizada, qualidade do complexo capsuloligamentar, presença da lesão de Bankart, presença de lesão de Hill-Sachs, presença de erosão da borda anteroinferior da cavidade glenoidal, entre outros (6)(7)(8)(9)(10)(11)(12) . Alguns autores relatam que o fator mais determinante para a recidiva seja a idade do paciente no momento do primeiro episódio de luxação, estando os menores de 18 anos mais suscetíveis a apresentar recidiva da luxação, chegando a índices de até 86,7% (6,7,10,11) . Gartsman et al (3) observaram aumento na gravidade das lesões labiais durante a artroscopia em pacientes com mais de três episódios de luxação; contudo, isso não influiu de maneira negativa nos resultados da cirurgia, inclusive nos índices de recidiva pós-operatória.…”
Section: Resultsunclassified